Charismatic Kyai Leadership and Educational Management in Mahir Watusalam Pekalongan Islamic Boarding School - Nurlaila Ana (Universitas Negeri Semarang, 2023)
The uniqueness of the leadership style and management of Islamic Education in the development of the Mahir Watusalam Islamic Boarding School, Pekalongan Regency, Central Java, Indonesia is very interesting because of the charismatic influence of its leadership. This research aims to analyze the charismatic leadership of the Kiai in the management and development of Islamic education at the Mahir Islamic Boarding School. Descriptive research methodology with a qualitative approach and research location at the Mahir Watusalam Islamic Boarding School, Pekalongan Regency. Data collection techniques with interviews, documentation, and observation studies. The results of the research are the Kyai's leadership style which can build and develop the Mahir Islamic Boarding School; the leadership of the Kiai in motivating ustad, followers, sympathizers, and parents of students in attending education at Islamic boarding schools; the leadership function of the Kiai in providing direction to the ustad, santri and their followers to be able to participate in and develop the pesantren implementation program; the impact of the Kiai's leadership that can provide the implementation of pesantren education management. An important finding from this research is that to develop education in Islamic boarding schools in the modern era, a kiai must master in-depth knowledge and knowledge, both general and religious knowledge, and role model.